Self-Efficacy of Preservice Mathematics Teachers toward Teaching in Inclusive Classrooms - Putranto, Sumbaji (The Center for Disability Studies and Services Brawijaya University, 2025)
Teacher self-efficacy is a crucial factor for successful learning in inclusive classrooms. This study explores the self-efficacy of preservice mathematics teachers to teach in inclusive classes. The study used an exploratory sequential design through a survey and continued with interviews. The survey stage involved seventy-seven participants. The survey data were analyzed descriptively followed by semi-structured interviews with ten participants selected using purposive sampling. Qualitative data were analyzed using the Bogdan & Biklen technique. The results showed that aspects of self-efficacy in using mathematics-inclusive instruction and managing behavior were in the moderate category. Experience with inclusive education lectures, training, and interactions with students with disabilities (SWD) influence these aspects. However, self-efficacy in collaborations is in the low category. The majority of participants express worry about collaborating with external parties such as parents, doctors, and psychologists. This is due to limited experience in conducting collaboration. This finding is expected to be a recommendation for universities and related parties to organize education and training that facilitates preservice mathematics teachers to develop teaching skills in inclusive classroom.